The study on effectiveness of TRI-PHOL-THAT oil poultice in patients with low back pain syndrome - Jarukitsakul, Siriporn; Chatawatee, Bodin; Rueangsaksit, Chalita; Biakhaw, Phitchayanee; Padthong, Auaarree; Abdulloh, Bibifatilai (Health Science, Science and Technology Reviews, 2024)
Low back pain is an exceptionally common musculoskeletal problem that significantly impacts the patient's daily activities and quality of life. The goal of this quasi-experimental research was to determine the effectiveness of Tri-Phol-That oil poultice in the treatment of patients with low back pain, Traditional Thai Medicine Hospital, Prince of Songkla University. The study was conducted between December 2022 and March 2023 in 2 participating groups that received Tri-Phol-That oil poultice (n=23) and sesame oil poultice (n=23) for thirty minutes at a time, five consecutive days. Treatment outcomes were evaluated by assessing the impact of low back pain using the Modified Oswestry low back pain disability questionnaire, pain score and assessment of the flexibility of the back muscles. Data were analyzed using descriptive and inferential statistics. The study revealed that the Tri-Phol-That oil poultice and sesame oil poultice for five consecutive days significantly reduced the effects of low back pain and reduced the level of pain (p < 0.05) and influenced muscular flexibility was found. Therefore, it can be concluded that oil poultice procedures with Tri-Phol-That oil and sesame oil is effective to relieve lower back pain in patients as their results are approximately similar. Can be used as a guideline for the study and development of clinical practice guidelines as a complementary intervention for the treatment of low back pain in Thai traditional medicine.